THE ANALYSIS OF PRESCRIBED PEDAGOGY PRACTICES FOR DESIGN AND TECHNOLOGY IN ZAMBIAN SCHOOLS. THE CASE OF CHIPATA DISTRICT - Mhango, Mabvuto Dweku; Ndenguma, Dr. Dickson. D; Mnelemba, Mr. M. (Journal of Education and Practice, 2021)
Purpose: The study delved into prescribed pedagogy practices for Design and Technology in Zambian schools, "Chipata district in particular". The main objective of this study was to contribute towards a comprehensive understanding of the prescribed pedagogies in the syllabus of Design and Technology. Thus, the rationale of the work is based on the application of prescribed pedagogies by practicing teachers for Design and Technology in the teaching and learning process in secondary schools. The, aim of the study is to analyse the application of the prescribed methods by teachers of Design and Technology. The research was undertaken in order to assess the application of the prescribed pedagogy in the newly rolled out curriculum for Design and Technology. This was on the premise that the curriculum was implemented without retraining of the subject teachers. The study covers three selected schools, from which six practicing teachers and three pupils were interviewed. Methodology: Data was collected through interviews, documented records used by the teachers and class observation. The collected data was analysed manually and through the use of qualitative data analysis (QDA) miner lite. During the data analysis themes emerged which served as a guide for discussion. Results: The study indicates that teachers need more orientation of the pedagogies in the syllabus to fully utilise them. Further, results show that there is need to enhance teacher content knowledge and ensure the availability of teaching and learning resources. For the sake of good application of the pedagogies the study recommends: orientation of teachers on prescribed teaching methods, provision of standard workroom, enough teaching and learning resources, and upgrading teacher qualifications. Unique contribution to theory, policy, and practice: Teachers need to read and understand the new syllabus demands for them to apply the prescribed pedagogies as required. Additionally it is great importance to orient teachers adequately before the new syllabus is rolled out. Therefore there is need to a deliberate program to retrain teachers or organize continuous professional development programs so that they are acquainted to new pedagogies.